Gender Conflicts on the Shopfloor: Barcelona Women at Chocolates Amatller, 1890–1914 - Jou-Badal, Xavier (International review of social history, 2024)
The cry of “Get married women out of the factories!” echoed across the Spanish industrial landscape at the turn of the twentieth century, driven by two intertwined factors. From a societal perspective, women's place was at home, not in factories. On an economic note, concerns arose over women's lower wages displacing men from jobs. This research delves into a case study of a workers’ claim aimed against women. It aims to illuminate the interplay of social demands and gender dynamics in labour history and business operations. Using as a case study a strike among male workers at the Amatller chocolate factory in May 1890, it seeks insights into gender complexities and women's challenges when joining the workforce. Male factory workers sought better conditions but directed their frustrations at women, influenced by prevailing social discourse. Women joined the factory, but portraying them as victors would be an oversimplification. Their presence was restricted, confined to manual tasks, with few opportunities for advancement.